Relationship preserving auction for repeated e-procurement - Park J. (Institutional Knowledge at Singapore Management University, 2008)
While e-procurement auction has helped firms to achieve lower procurement costs, auction mechanisms that prevail at present in procurement markets need to address an important issue that concerns the ability to maintain long term relationships with the partners, especially in repeated e-procurement settings. In this paper, we propose a Relationship Preserving Auction (RPA) mechanism that augments the conventional auction mechanism with a bidder relationship scoring model. Our proposed mechanism gives increased chances of winning to the bidders who have bidden at relatively competitive price but had comparatively less wins so far. Keeping these bidders in the auction over time will lead to more competitive bidding prices and eventually reduce the auctioneer's total procurement cost in repeated auctions. From simulation experiments, we show how RPA works under different bidders' behavior. We show that RPA is able to obtain lower procurement cost compared to conventional procurement auctions when bidders bid opportunistically and renege readily to other markets.